Economic thinking of tax management policies from the focus of tax evasion in Ecuador - Sanandrés Álvarez, Luis; Vallejo Altamirano, Danilo; Ruiz Salgado, Myriam (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
A democratic and social rule of law, taxation is an instrument of society to achieve its own objectives, which must focus on economic and social development, to promote the productive, educational, and scientific sector; then tax management is the effective control mechanism based on the principles, the research aims to determine the relationship between economic thinking and taxpayers' perception of tax policy and tax evasion. The methodology used is a mixed approach, supported by the descriptive documentary study, based on the bibliographic and digital review, it should be noted how tax policies have had relevant results in reference to collection, which is consistent with economic thinking, because evidence in the years since 2000 the thought was neoliberal the collection is low, while from 2007 to 2016 with the revolutionary socialist thought there is an increase in the collection. On the other hand, new tax reforms are suggested by creating a tax equity law; which allows changes to improve tax revenue regardless of the political ideological thinking of the government in office; what is important is social equality with fiscal equity. Therefore, there must be a relationship between taxpayers with tax policies and tax evasion. This relationship must generate trust so that the country can develop and satisfy social inclusion policies and improve the quality of life through a new society with ethics and morals.